1985
DOI: 10.1136/bmj.291.6509.1617
|View full text |Cite
|
Sign up to set email alerts
|

Mid-arm and chest circumferences at birth as predictors of low birth weight and neonatal mortality in the community.

Abstract: In developing countries, where about three quarters of births occur at home or in the community, logistic problems prevent the weighing of every newborn child. A study was performed to see whether other simpler measurements could be substituted for weight to identify neonates of low birth weight and those at risk.A study of 520 hospital births showed a strong correlation (p<0-001) between other anthropometric variables and birth weight, but the correlation was maximum for chest circumference (r=0-8696) and mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
59
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 4 publications
(1 reference statement)
9
59
0
Order By: Relevance
“…These findings were consistent with findings of Vaquera et al (10) who observed arm circumference had the highest correlation (r=0.92) with birth weight followed by chest circumference (r=0.86), head circumference (r=0.79) and length (0.78). The present findings were similar to findings of some other works (11-14) but were not consistent to study conducted by researchers (15,16).…”
Section: Discussionsupporting
confidence: 82%
“…These findings were consistent with findings of Vaquera et al (10) who observed arm circumference had the highest correlation (r=0.92) with birth weight followed by chest circumference (r=0.86), head circumference (r=0.79) and length (0.78). The present findings were similar to findings of some other works (11-14) but were not consistent to study conducted by researchers (15,16).…”
Section: Discussionsupporting
confidence: 82%
“…So other anthropometric measurements like head circumference, chest circumference, mid arm circumference become important [3] and some of them like chest circumference and mid arm circumference can be used as surrogate markers for birth weight. [4] Many studies were carried out to evaluate the mid arm circumference (MAC) and chest circumference as an alternative indicator of low birth weight. So the present study attempts to establish the norms for our populations.…”
Section: Introductionmentioning
confidence: 99%
“…These studies likely overestimated the correlation between these surrogate measures and birth weight because they used limited numbers of highly trained personnel (Bhargava et al, 1985;Sharma et al, 1989;Huque and Hussain, 1991;Walraven et al, 1994;Arisoy and Sarman, 1995;Ahmed et al, 2000). Furthermore, infants born and/or measured in hospitals may not be representative of those born in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, efforts have been made to identify more easily measured anthropometric surrogates for birth weight. A number of studies have focused on measuring the circumference of the head, chest, mid upper-arm, thigh or calf and observed the correlation with continuous measurements on a gold standard weighing scale (Bhargava et al, 1985;Ramji et al, 1986;Singh et al, 1988;Ngowi et al, 1993;WHO Collaborative Study of Birth Weight Surrogates, 1993;Raymond et al, 1994;Arisoy and Sarman, 1995;Kapoor et al, 1996;Dhar et al, 2002;Naik et al, 2003). In general, chest circumference has performed better than other measures and has been recommended for continued investigation (ACC/SCN, 2000), although investigators have demonstrated correlations between birth weight and mid upper-arm circumference (Sauerborn et al, 1990), calf (Gupta et al, 1996;Samal and Swain, 2001) or thigh (Sharma et al, 1989) that are as strong as with chest circumference.…”
Section: Introductionmentioning
confidence: 99%